Plasma calcium, inorgnic phosphorus and magnesium levels in buffaloes afflicted with metritis - ABDULLAH, FAYAZA; TIWARl, R P; KHAN, J R (The Indian Journal of Animal Reproduction, 2023)
Plasma leyels of calcium, inorganic phosphorus and magnesium during postpartum period were estimated in · 10 healthy and 10 buffaloes suffering from metritis. The buffaloes were selected randomly . Mean plasma calcium levels were higher in healthy than in affected buffaloes (9.80± 0.28 vs 7.57± 0.83 mg%, P>0.05). No difference in plasma level of inorganic phosphorus (5.52±0.74 vs 4.65±0.41mg %) and magnesium was observed. Serum calcium level was lower P<0.05) in affected buffaloes.